2022
DOI: 10.1155/2022/7100238
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Early Nutritional Assessment and Nutritional Support on Immune Function and Clinical Prognosis of Critically Ill Children

Abstract: The aim of this study was to study the effect of early nutritional assessment and nutritional support on immune function and clinical prognosis of critically ill children. 90 critically ill children at the same level of severity admitted to the pediatric intensive care unit (PICU) of our hospital (June 2019–June 2020) were chosen as the research objects and were equally separated into the experimental group and the control group by the random number table method. The children in the control group were admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…These results reflect what the other studies have demonstrated about the pivotal role of early assessment of critically ill patients by dieticians in pediatric ICUs [ 32 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…These results reflect what the other studies have demonstrated about the pivotal role of early assessment of critically ill patients by dieticians in pediatric ICUs [ 32 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Journal of Healthcare Engineering has retracted the article titled “Effect of Early Nutritional Assessment and Nutritional Support on Immune Function and Clinical Prognosis of Critically Ill Children” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled "Efect of Early Nutritional Assessment and Nutritional Support on Immune Function and Clinical Prognosis of Critically Ill Children" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%